Weak Quasielastic Hyperon Production Leading to Pions in the Antineutrino-Nucleus Reactions - Fatima, Atika; Athar, Mohammad Sajjad; Singh, S. K. (Frontiers in Physics, 2019)
In this review, we have studied the quasielastic production cross sections and polarization components of Λ, Σ0, and Σ− hyperons induced by the weak charged currents in the antineutrino reactions on the nucleon and the nuclear targets like 12C, 16O, 40Ar and 208Pb. It is shown that the energy and the Q2 dependence of the cross sections and the various polarization components can be effectively used to determine the axial vector transition form factors in the strangeness sector and test the validity of various symmetry properties of the weak hadronic currents like G-invariance, T-invariance and SU(3) symmetry. In particular, the energy and the Q2 dependence of the polarization components of the hyperons is found to be sensitive enough to determine the presence of the second class current with or without T-invariance. These hyperons decay dominantly into pions giving an additional contribution to the weak pion production induced by the antineutrinos. This contribution is shown to be quantitatively significant as compared to the pion production by the Δ excitation in the nuclear targets in the sub-GeV energy region relevant for the ν̄μ cross section measurements in the oscillation experiments. We have also included a few new results, based on our earlier works, which are in the kinematic region of the present and future (anti)neutrino experiments being done with the accelerator (anti)neutrinos at T2K, MicroBooNE, MiniBooNE, NOνA, MINERνA, and DUNE, as well as for the atmospheric (anti)neutrino experiments in this energy region.